2(n - 1) + 4n = 2(3n - 1)
2n - 2 + 4n = 6n -2
6n - 2 = 6n - 2 (equal)
6n - 6n = 2 - 2
0 = 0
whatever value you put into the place of n, you'll get 0 = 0
Answer:
False
Step-by-step explanation:
EU and the US are very good friends and they often trade with them.
Answer:
#############################
I can add u to a snap gc where we help each other with work
Answer:
![Area =55.4ft^2](https://tex.z-dn.net/?f=Area%20%3D55.4ft%5E2)
Step-by-step explanation:
Given
The attached rhombus
Required
The area
First, calculate the length of half the vertical diagonal (x).
Length x is represented as the adjacent to 60 degrees
So, we have:
![\tan(60) = \frac{4\sqrt 3}{x}](https://tex.z-dn.net/?f=%5Ctan%2860%29%20%3D%20%5Cfrac%7B4%5Csqrt%203%7D%7Bx%7D)
Solve for x
![x = \frac{4\sqrt 3}{\tan(60)}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B4%5Csqrt%203%7D%7B%5Ctan%2860%29%7D)
![\tan(60) = \sqrt 3](https://tex.z-dn.net/?f=%5Ctan%2860%29%20%3D%20%5Csqrt%203)
So:
![x = \frac{4\sqrt 3}{\sqrt 3}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7B4%5Csqrt%203%7D%7B%5Csqrt%203%7D)
![x = 4](https://tex.z-dn.net/?f=x%20%3D%204)
At this point, we have established that the rhombus is made up 4 triangles of the following dimensions
![Base = 4\sqrt 3](https://tex.z-dn.net/?f=Base%20%3D%204%5Csqrt%203)
![Height = 4](https://tex.z-dn.net/?f=Height%20%3D%204)
So, the area of the rhombus is 4 times the area of 1 triangle
![Area = 4 * \frac{1}{2} * Base * Height](https://tex.z-dn.net/?f=Area%20%3D%204%20%2A%20%5Cfrac%7B1%7D%7B2%7D%20%2A%20Base%20%2A%20Height)
![Area = 4 * \frac{1}{2} * 4\sqrt 3 * 4](https://tex.z-dn.net/?f=Area%20%3D%204%20%2A%20%5Cfrac%7B1%7D%7B2%7D%20%2A%204%5Csqrt%203%20%2A%204)
![Area =2 * 4\sqrt 3 * 4](https://tex.z-dn.net/?f=Area%20%3D2%20%2A%204%5Csqrt%203%20%2A%204)
![Area =55.4ft^2](https://tex.z-dn.net/?f=Area%20%3D55.4ft%5E2)